The Effect of Picture Teaching Media to the Ability of Grade 7th Students in English Vocabulary Mastery of SMP Yayasan Perguruan Keluarga (YPK) Pematangsiantar - Rizky Khairunnisa Sormin; Fitri Rizki; Ika Purnama Sari; S Susiani (ITScience (Information Technology and Science), 2022)
English is an international language that use by many people in this world. Human used English to make communication in daily life. It can help human to make connection with other people, nation country in this world to get information. As we know in learning English there are four skills, they are: speaking, listening, writing, and reading. Vocabulary is also an essential skill for learning to read, speak, write and listen. Without sufficient vocabulary, people cannot communicate and express their feeling both in form of spoken and written effectively. Nowadays, the students must improve their vocabulary because in their school, they are not only learning vocabulary in English lesson, but also in other books, there are also some English vocabularies that must be known by students. In improving student vocabulary, the students need some method or technique. The used picture of media will be needed to help the students in teaching-learning vocabulary. Picture is one of visual material in teaching that well established. This researcher experience at learning practice program in SMP YPK Pematangsiantar, many of students were lack of vocabularies.The students had many problems in mastering English words and this situation made them to be lazy to study English. One of the strategies can be used to solve the problems in teaching English is using media. As what have been mentioned previously, the purpose of this research was to find out the effect by uding Picture media on students’ ability in english vocabulary at grade seventh SMP YPK. Researcher chose two classes as the sample that divided into two groups are VII-6 as Experimental Group and VII-4 as Control Group. From all the analyzed data, it is found that there was a significant using Picture media on students’ ability in English Vocabulary at grade seventh SMP YPK Pematangsiantar. It shows that the result of t-test was higher than t-table (5.02>1.67), therefore the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) was accepted.Based on the result of the research, it was concluded that by using Picture media on students’ ability in English Vocabulary is most effective.